Underestimation of pregnancy risk among women in Vietnam - Jessica Londeree; Nghia Nguyen; Linh H. Nguyen; Dung H. Tran; Maria F. Gallo (BMC, 2020)
Abstract Background Addressing women's inaccurate perceptions of their risk of pregnancy is crucial to improve contraceptive uptake and adherence. Few studies, though, have evaluated the factors associated with underestimation of pregnancy risk among women at risk of unintended pregnancy. Methods We assessed the association between demographic and behavioral characteristics and underestimating pregnancy risk among reproductive-age, sexually-active women in Hanoi, Vietnam who did not desire pregnancy and yet were not using highly-effective contraception (N = 237). We dichotomized women into those who underestimated pregnancy likelihood (i.e., 'very unlikely' they would become pregnant in the next year), and those who did not underestimate pregnancy likelihood (i.e., 'somewhat unlikely,' 'somewhat likely' or 'very likely'). We used bivariable and multivariable logistic regression models to identify correlates of underestimating pregnancy risk. Results Overall, 67.9% (n = 166) of women underestimated their pregnancy risk. In bivariable analysis, underestimation of pregnancy risk was greater among women who were older (> 30 years), who lived in a town or rural area, and who reported that it was "very important" or "important" to them to not become pregnant in the next year. In multivariable analysis, importance of avoiding pregnancy was the sole factor that remained statistically significantly associated with underestimating pregnancy risk (odds ratio [OR]: 0.11; 95% confidence interval [CI], 0.05-0.25). In contrast, pregnancy risk underestimation did appear to vary by marital status, ethnicity, education or other behaviors and beliefs relating to contraceptive use. Conclusions Findings reinforce the need to address inaccurate perceptions of pregnancy risk among women at risk of experiencing an unintended pregnancy.